2022
DOI: 10.1111/jnu.12863
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to primary care engagement for people who inject drugs: A systematic review

Abstract: Introduction People who inject drugs (PWID) have a greater burden of multimorbid chronic diseases than the general population. However, little attention has been paid to the engagement in primary care for services related specifically to injection drug use and management of underlying chronic comorbid diseases for this population. This systematic review identified facilitators and barriers to healthcare engagement in the primary care setting among PWID. Design and Methods Studies were identified by a literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…61-63 Given that OPCs are healthcare settings with trained staff, these environments are well positioned to address the medical consequences of an unpredictable drug supply; this is especially important for people who might not be able to access—or might feel uncomfortable in—traditional medical settings due to established barriers such as the cost of care, anticipated stigma, and access to health insurance. 64,65 In addition, OPCs can provide broader health and wellness services to clients such as food, clothing, and showers. 15,64…”
Section: Public Health Outcomes Of Opcsmentioning
confidence: 99%
“…61-63 Given that OPCs are healthcare settings with trained staff, these environments are well positioned to address the medical consequences of an unpredictable drug supply; this is especially important for people who might not be able to access—or might feel uncomfortable in—traditional medical settings due to established barriers such as the cost of care, anticipated stigma, and access to health insurance. 64,65 In addition, OPCs can provide broader health and wellness services to clients such as food, clothing, and showers. 15,64…”
Section: Public Health Outcomes Of Opcsmentioning
confidence: 99%
“…Authors from one systematic review showed that PWID utilize emergency department services 4.8 times more than the general population, with multiple studies showing injection drug use as a strong predictive factor of increased ED visits (Kendall et al, 2017; Lewer et al, 2020; Nambiar et al, 2017). In another systematic review younger age, incarceration, homelessness, lack of health insurance, and poor provider continuity are associated with decreased engagement in primary care for PWID (Heidari et al, 2023), while visits with a primary care provider (PCP) and receipt of MOUD are strong protective factors against ED utilization (Kendall et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies included in this special issue address substance abuse among different age and cultural groups. These included studies focused on alcohol and substance use among Native American youth in the United States (Lowe et al, 2024), tobacco and alcohol co‐use among college graduates in Spain (Neddermann‐Carrillo et al, 2024), and people who inject drugs (PWID) in the United States (Heidari et al, 2023). Taken together, these studies highlight unique challenges and opportunities for addressing substance abuse across the lifespan and through a multitude of community‐based and healthcare responses.…”
mentioning
confidence: 99%
“…The observational research reported among adult college graduates from the “Seguimiento Universidad de Navarra” (SUN) cohort study in Spain ( n = 7175) (Neddermann‐Carrillo et al, 2024) and qualitative research with PWID (Heidari et al, 2023) help identify opportunities for interventions. Findings from SUN highlight important demographic, behavioral factors, and personality factors that can be used to identify sub‐populations at the highest risk for alcohol and tobacco co‐use (e.g., more frequent coffee drinkers) and protective characteristics that can be leveraged (e.g., promoting physical activity).…”
mentioning
confidence: 99%
See 1 more Smart Citation